Asosiasi Polimorfisme Mikrosatelit DRBP1 Gen BoLa (Bovine Leucocyte Antigen) dengan Ukuran Tubuh pada Sapi Bali - Patmawati, Ni Wayan; Wandia, I Nengah; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 2 No 2 (2014), 2014)
Genomic selection has a potency for improving the genetic quality of livestock. In effort to find out a molecular marker or DNA segment which is linked with a certain phenotype, we examined the association of the polymorphism of microsatellite DRBP1 with the body size of Bali cattle. A total of 55 blood samples of sires was collected from the Breeding Center of Bali Cattle Improvement Office in District of Jembrana. Total DNA was extracted with QIAamp DNA blood mini kit. The locus was amplified using PCR technique and alleles were separated through PAGE 6%, and visualized with silver staining. We found 5 alleles which their length varied from 108 bp to 136 bp. Allele 122 had the highest frequencies (25.45%). The expected heterozygositiy (HE) and observed heterizygosities (HE), and the PIC were 0.783, 0.891 and 0.738 consecutively. Statistic analysis showed that the polymorphism of microsatellite DRBP1 had no significant association (p > 0.05) with body size of male Bali cattle. This indicates that the DRBP1 does not play a role in determining the body size.
Keywords: Bali cattle, BoLA gene, DRBP1 microsatellite, Body zise